Effect of 1450 ppm Fluoride Toothpaste in Remineralization of Incipient Carious Lesions: An In Vitro Study - Soontharotoke, Penarsan; Govitvattana, Nattanan (Khon Kaen University Dental Journal, 2023)
The aim of this study was to compare the remineralization effect of 1000 and 1450 ppm fluoride toothpaste on artificial enamel carious lesion. Thirty enamel specimens with artificial carious lesions were randomly assigned into 3 groups: 1) artificial saliva 2) 1000 ppm fluoride toothpaste 3) 1450 ppm fluoride toothpaste. The specimens were subject to 14-day pH cycling, the treatment groups were immersed in fluoride toothpaste solution for 2 minutes twice a day during the pH cycling phase. The percentage of fluorescence loss ( F) was measured using the quantitative light-induced fluorescence-digital machine (QLF-D). The change of percentage of fluorescence loss ( F) was determined. The results showed that F in fluoride toothpaste groups were significantly greater than in the control group. The 1450 ppm fluoride toothpaste group showed significantly higher F compared to 1000 ppm fluoride toothpaste group (p=0.042). In conclusion, the results from this study demonstrated that the use of 1450 ppm fluoride toothpaste significantly increased remineralization of artificial enamel carious lesions than the use of 1000 ppm fluoride toothpaste.